KEDUDUKAN ALAT BUKTI ELEKTRONIK DALAM PUTUSAN PERCERAIAN DI PENGADILAN AGAMA YOGYAKARTA - Nashir, Fatah; Mustafida, Latifa (Fortiori Law Journal, 2021)
Along with the development of technology, people are starting to turn to digital technology in proving cases. In some divorce cases, electronic evidence is used to prove the dispute in divorce. This study aims to determine the function of electronic evidence in the divorce process on the pretext of irreconcilable husband and wife disputes. The aim is to find out the judges' views on the validity of electronic evidence (ABE) in their efforts to produce divorce case decisions.This research is a normative juridical type. The research data is sourced from the decision No. 0150/Pdt.G/2014/PA.Yk & Number 0132/Pdt.G/2015/PA.Yk. Secondary data will be taken from literature or literature studies that support the decision, namely the ITE Law, Marriage Law, Compilation of Islamic Law, Civil Code, Supreme Court Regulations regarding electronic evidence. Furthermore, the data will be analyzed deductively and descriptively.The results of the study stated that the judge had accepted ABE as one of the evidence used in divorce cases. The acceptance by the judges is done with limitations. The limitation is because ABE has not been recognized in the Civil Code, BW or RBg. In addition, electronic evidence sourced from the Law on Information and Electronic Transactions is still very general in nature so that ABE acceptance is only used as initial evidence, provided that it has been recognized and adjusted to the applicable trial procedures and confirmed by experts, in order to clarify the facts of the dispute. in divorce cases.